2003
DOI: 10.1074/jbc.m308610200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Na,K-ATPase by the γ Subunit

Abstract: The enzymatic activity of the Na,K-ATPase, or sodium pump, is modulated by members of the so-called FXYD family of transmembrane proteins. The best characterized member, FXYD2, also referred to as the ␥ subunit, has been shown to decrease the apparent Na ؉ affinity and increase the apparent ATP affinity of the pump. The effect on ATP affinity had been ascribed to the cytoplasmic C-terminal end of the protein, whereas recent observations suggest that the transmembrane (TM) segment of ␥ mediates the Na ؉ affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Moreover, mutational analysis has revealed that the TM domain of FXYD7 plays a role in the structural and functional interaction of FXYD7 (6). Similar conclusions were drawn for FXYD2 and FXYD4 (7)(8)(9).…”
supporting
confidence: 64%
“…Moreover, mutational analysis has revealed that the TM domain of FXYD7 plays a role in the structural and functional interaction of FXYD7 (6). Similar conclusions were drawn for FXYD2 and FXYD4 (7)(8)(9).…”
supporting
confidence: 64%
“…Nevertheless, a clear distinction between interaction sites involved in the stable association or in a specific functional effect is not obvious in all cases. Based on experiments with mimetic peptides, it has indeed been proposed that Gly 41 (corresponding to Gly 40 in FXYD7) is not primarily involved in Na,K-ATPase interaction but rather mediates the effect on the Na ϩ kinetics of FXYD2 (34). Knowing that FXYD7 has no effect on the apparent Na ϩ affinity of Na,K-ATPase, this result is difficult to reconcile with our results which show that a G40A mutant of FXYD7, decreases the association efficiency and completely abolishes the K ϩ effect.…”
Section: Discussionmentioning
confidence: 99%
“…Co-immunoprecipitation-The method used was a modification of Garty et al (27) as described elsewhere (21). Band densities were quantified using Molecular Dynamics ImageQuant software.…”
Section: Of the Lowry Methods (26)mentioning
confidence: 99%